Comparative study on organoleptic properties and volatile organic compounds in turmeric, turmeric essential oil, and by-products using E-nose, HS-GC-IMS, and HS-GC-MS - Bing Yang; Wanjia Wang; Jianuo Zhang; Wei Gao; Lipeng Fan; Bimal Chitrakar; Yaxin Sang (Food Chemistry: X)
The properties, applications, and in vitro bioactivities of turmeric, turmeric essential oil (TEO), and turmeric essential oil by-products (TEO-BP) were evaluated using sensory analysis, gas chromatography–mass spectrometry (GC–MS), gas chromatography-ion mobility spectrometry (GC-IMS), and electronic nose techniques. A total of 62 and 66 volatile organic compounds (VOCs), primarily terpenoids and sesquiterpenoids, were identified by GC–MS and GC-IMS, respectively. Distillation temperature, particularly at 90 °C, significantly influenced the color and organoleptic properties of TEO, with variations in VOC profiles driving these differences. Molecular distillation at 90 °C was found to optimize the purification and concentration of key VOCs in TEO. All turmeric samples demonstrated robust antioxidant and α-glucosidase inhibitory activities, with TEO-90 exhibiting the highest bioactivity. These results underscore the potential applications of TEO and TEO-BP in food and nutraceutical industries, offering a sustainable strategy to reduce waste and enhance the efficient utilization of turmeric resources.